2003
DOI: 10.1021/tx034093k
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Aided Knowledge Generation for Understanding Skin Sensitization Mechanisms: The TOPS-MODE Approach

Abstract: The TOPS-MODE (topological substructural molecular descriptors) approach is used to derive models for understanding the molecular structural contribution to skin sensitization. A data set of 93 compounds was used in the development of the models; 29 new skin sensitization values (EC3) are reported here for the first time. The models developed possess high predictivity and have been validated through the use of cross-validation and external validation sets. The models have enabled the formulation of potential n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 54 publications
1
47
0
Order By: Relevance
“…Modelling structural determinants of skin sensitisation (Estrada, et al, 2003) QSAR of Phenol Toxicity (Hall and Vaugh, 1997) …”
Section: Molecular Weight (Mw) and Molecular Volume (Mv)mentioning
confidence: 99%
See 1 more Smart Citation
“…Modelling structural determinants of skin sensitisation (Estrada, et al, 2003) QSAR of Phenol Toxicity (Hall and Vaugh, 1997) …”
Section: Molecular Weight (Mw) and Molecular Volume (Mv)mentioning
confidence: 99%
“…In this example a model for skin sensitisation was developed relating the potency of a set of 93 diverse chemicals to a range of topological indices (Estrada et al, 2003). The indices used in the final model accounted for hydrophobicity (H), polar surface area (PS), molar refractivity (MR), polarisability (PSR), charges (GM), van der Waals radii (VDW).…”
mentioning
confidence: 99%
“…An automatic knowledge generator is a methodology that will provide new structural alerts to the knowledge archive in a cyclic way keeping it updated. In previous works [54][55][56] we have shown that the so-called topological sub-structural molecular design (TOPS-MODE) approach [57][58][59][60][61][62] represents a useful platform for the automatic generation of toxicological structural alerts. In these works a general strategy for knowledge flow concerning skin sensitization and chromosome aberrations based on the combined use of TOPS-MODE and DEREK expert system was proposed [54][55][56].…”
Section: Necessity For Automated Rule-extractionmentioning
confidence: 99%
“…Final rating Basketter and Gerberick [1996] no data Buehler unpublished at 30% only no data OECD no 3 Maisey and Miller [1986] yes MEST yes at 30% only no data only 10 yes 3 Klecak et al [1977] no data GPMT yes yes no data only 6 yes 3 Klecak et al [1977] no data OET yes yes no data 8/dose yes 3 Klecak et al [1977] no data FCAT yes yes no data no data no 3 Klecak et al [1977] no data Draize yes yes no data 8 yes 3 Senma et al [1978] no data GPMT yes 1% topical no data only 9 no 3 Epstein [1977] no data HMT yes no, at 6% no data 25 yes 2 Kligman [1973] no data HMT yes no, at 6% no data 25 yes 2 Greif [1967] no data HMT yes no, at 6% no data 25 no 2 Epstein [1977] no data HMT yes no, at 6% no data 27 and 30 tested in presence of cinnamic alcohol 1 Harrison et al [1994a] no data HRIPT yes no, at 20% no data 95 yes 3 Harrison et al [1994b] no Topological Substructural Molecular Descriptors TOPS-Mode (topological substructural molecular descriptors) uses molecular structural elements as basis to derive models for skin sensitization [Estrada et al, 2003]. Identifying a carbonyl group in conjugation with a double bond as structural alerts for a Michael (nucleophilic) addition reaction, ACA is classifi ed as a weak allergen.…”
Section: Structure-activity Relationships Predictive Of Sensitizationmentioning
confidence: 99%